The ethics of facing the Other in suicide. (January 2022) - Jaworski, Katrina
Despite a plethora of existing literature on the topic of suicide, very little attention has been given to research ethics in practice in research on suicide. When suicide research does pay attention to the ethical issues researchers are likely to face, the focus is on the roles institutional human ethics review committees fulfil to ensure ethical conduct in all stages of research. In response to this problem, this article focuses on the philosophical relationship between qualitative methodology and research ethics in the context of researching queer youth suicide. In so doing, I draw on my experiences of interviewing gender-and sexually diverse young people about their familiarity with suicide. These experiences are based on a qualitative pilot study I conducted on queer youth suicide, which used the unstructured interview technique to collect data. Drawing on the works of Emmanuel Levinas and Judith Butler, I examine what it means to face the alterity of the suicidal 'Other', and what this facing entails in terms of research ethics as relational. I argue that facing reveals not only myself as more vulnerable than I anticipated, but also the suicidal 'Other' as agentic instead of only vulnerable and at-risk of suicide.